Pre-disinfectant effect of copper oxychloride on fungal contaminants in nodal segments of Guadua angustifolia Kunth, for in vitro establishment (Revista de Investigaciones Universidad del Quindío, 2012)
In in vitro establishment of plant tissues, we report the implementation status of disinfection protocols, with litt-le information about pre-disinfection processes after explants were selected, according to species. At different stages of micropropagation of Guadua angustifolia there are reports of fungi and bacteria contamination, being the one with fungus more related to the establishment phase, while the presence of bacteria was recorded at all in vitro stages. For this reason, at the Biotechnology Laboratory, of the Autonomous Regional Corporation of Quindío, Colombia, we proceeded to evaluate different pretreatment disinfection of nodal segments on bamboo, accompanied by a disinfection protocol already established, consisting of 90% alcohol for 3 min, followed by immersion in NaClO of 3% for 10 min. the pre-disinfection was carried out by commercial detergent wash in sterile distilled water for 20 min. then the different nodal segments (youth, mature and differentiated) were exposed to solutions of commercial products: copper oxychloride and Agrodyne and it’s mix for 30 min and 60 min. The lower rates of fungal contamination were obtained with young and mature nodal segments subjected to copper oxychloride, while the juvenile nodal segments showed higher bacterial contamination.
Keywords: plant tissue; protocols; disinfection; nodal segment; establishment